To find the solution to the compound inequality -2 ≤ 2x + 1/3 - 4 < 1, we first need to isolate x.
We can start by adding 4 to all parts of the compound inequality:
-2 + 4 ≤ 2x + 1/3 - 4 + 4 < 1 + 4
This simplifies to:
2 ≤ 2x + 1/3 < 5
Next, we can subtract 1/3 from all parts of the compound inequality:
2 - 1/3 ≤ 2x + 1/3 - 1/3 < 5 - 1/3
This simplifies to:
5/3 ≤ 2x < 14/3
Finally, we can divide all parts of the compound inequality by 2 to solve for x:
(5/3)/2 ≤ (2x)/2 < (14/3)/2
This simplifies to:
5/6 ≤ x < 7/3
Therefore, the solution to the compound inequality is expressed as the set:
{x | 5/6 ≤ x < 7/3}
Which set expresses the solution to the compound inequality -2 _< 2x + 1/3 - 4 < 1?
7 answers
Which set expresses the solution to the compund inequility -2 _< 2x + 1/3 - 4 < 1?
A. { x : 3 _< x <7}
B. { x : 5/2 _< x < 1}
C. { x : -3/2 _< x < 1 }
D. { x : 5/2 _< x < 7 }
A. { x : 3 _< x <7}
B. { x : 5/2 _< x < 1}
C. { x : -3/2 _< x < 1 }
D. { x : 5/2 _< x < 7 }
To find the solution to the compound inequality -2 ≤ 2x + 1/3 - 4 < 1, let's solve each inequality separately.
First, let's solve -2 ≤ 2x + 1/3 - 4. We can start by adding 4 to both sides of the inequality:
-2 + 4 ≤ 2x + 1/3 - 4 + 4
2 ≤ 2x + 1/3
Next, let's isolate 2x by subtracting 1/3 from both sides:
2 - 1/3 ≤ 2x + 1/3 - 1/3
2 - 1/3 ≤ 2x
6/3 - 1/3 ≤ 2x
5/3 ≤ 2x
Now, let's solve 2x + 1/3 - 4 < 1. We can start by adding 4 to both sides of the inequality:
2x + 1/3 - 4 + 4 < 1 + 4
2x + 1/3 < 5
Now, let's isolate 2x by subtracting 1/3 from both sides:
2x + 1/3 - 1/3 < 5 - 1/3
2x < 14/3
Finally, let's isolate x by dividing both sides by 2:
(2x)/2 < (14/3)/2
x < 7/3
Combining the results, we have:
5/3 ≤ x < 7/3
Therefore, the correct answer is:
D. { x : 5/2 _< x < 7 }
First, let's solve -2 ≤ 2x + 1/3 - 4. We can start by adding 4 to both sides of the inequality:
-2 + 4 ≤ 2x + 1/3 - 4 + 4
2 ≤ 2x + 1/3
Next, let's isolate 2x by subtracting 1/3 from both sides:
2 - 1/3 ≤ 2x + 1/3 - 1/3
2 - 1/3 ≤ 2x
6/3 - 1/3 ≤ 2x
5/3 ≤ 2x
Now, let's solve 2x + 1/3 - 4 < 1. We can start by adding 4 to both sides of the inequality:
2x + 1/3 - 4 + 4 < 1 + 4
2x + 1/3 < 5
Now, let's isolate 2x by subtracting 1/3 from both sides:
2x + 1/3 - 1/3 < 5 - 1/3
2x < 14/3
Finally, let's isolate x by dividing both sides by 2:
(2x)/2 < (14/3)/2
x < 7/3
Combining the results, we have:
5/3 ≤ x < 7/3
Therefore, the correct answer is:
D. { x : 5/2 _< x < 7 }
What property of equality is displayed in step 3 in the solving of 9m + 4 - 7m = 5m +7/3?
The property of equality displayed in step 3 of the equation 9m + 4 - 7m = 5m + 7/3 is the addition property of equality.
In this step, we are combining like terms by adding the variable terms (9m and -7m) on the left side of the equation and the constant terms (4) on the left side of the equation.
Using the addition property of equality, we can simplify the equation to:
2m + 4 = 5m + 7/3
In this step, we are combining like terms by adding the variable terms (9m and -7m) on the left side of the equation and the constant terms (4) on the left side of the equation.
Using the addition property of equality, we can simplify the equation to:
2m + 4 = 5m + 7/3
Which linear equation has the same solution set as 9d/4 + 3 - 2d = -2 (3 + d) ?
A. 4w - 2 (7 - 3w) = w/3 - 6
B. 14 = 7/4 x - 19/4 + 2x
C. 35 - 15b = 95
D. 3x/5 - 10 = -7
A. 4w - 2 (7 - 3w) = w/3 - 6
B. 14 = 7/4 x - 19/4 + 2x
C. 35 - 15b = 95
D. 3x/5 - 10 = -7
To find the linear equation that has the same solution set as 9d/4 + 3 - 2d = -2(3 + d), we need to simplify the given equation and compare it to the options.
Let's simplify the given equation step by step:
9d/4 + 3 - 2d = -2(3 + d)
First, distribute the -2 to the terms in the parentheses:
9d/4 + 3 - 2d = -6 - 2d
Now, let's combine like terms by subtracting 2d from both sides:
9d/4 + 3 - 2d - (-2d) = -2d - (-2d) - 6
This simplifies to:
9d/4 + 3 = -6
Next, let's subtract 3 from both sides:
9d/4 + 3 - 3 = -6 - 3
This simplifies to:
9d/4 = -9
To isolate d, let's multiply both sides by 4/9:
(4/9)(9d/4) = (4/9)(-9)
This simplifies to:
d = -4
Now, let's compare the solution, d = -4, with the options:
A. 4w - 2(7 - 3w) = w/3 - 6: This equation is not equivalent to the given equation and does not have the same solution set.
B. 14 = 7/4x - 19/4 + 2x: This equation is not equivalent to the given equation and does not have the same solution set.
C. 35 - 15b = 95: This equation is not equivalent to the given equation and does not have the same solution set.
D. 3x/5 - 10 = -7: This equation does not have the same solution set as the given equation.
None of the options have the same solution set as the given equation 9d/4 + 3 - 2d = -2(3 + d).
Let's simplify the given equation step by step:
9d/4 + 3 - 2d = -2(3 + d)
First, distribute the -2 to the terms in the parentheses:
9d/4 + 3 - 2d = -6 - 2d
Now, let's combine like terms by subtracting 2d from both sides:
9d/4 + 3 - 2d - (-2d) = -2d - (-2d) - 6
This simplifies to:
9d/4 + 3 = -6
Next, let's subtract 3 from both sides:
9d/4 + 3 - 3 = -6 - 3
This simplifies to:
9d/4 = -9
To isolate d, let's multiply both sides by 4/9:
(4/9)(9d/4) = (4/9)(-9)
This simplifies to:
d = -4
Now, let's compare the solution, d = -4, with the options:
A. 4w - 2(7 - 3w) = w/3 - 6: This equation is not equivalent to the given equation and does not have the same solution set.
B. 14 = 7/4x - 19/4 + 2x: This equation is not equivalent to the given equation and does not have the same solution set.
C. 35 - 15b = 95: This equation is not equivalent to the given equation and does not have the same solution set.
D. 3x/5 - 10 = -7: This equation does not have the same solution set as the given equation.
None of the options have the same solution set as the given equation 9d/4 + 3 - 2d = -2(3 + d).